The relationship between stress and self-esteem among secondary schools students at Bachok, Kelantan / Suriyati Mohd Sukri - Mohd Sukri, Suriyati (2014)
The purpose of study was to know the relationship between source of stress and the self-esteem among student at five schools around Bachok area. This study involves 346 samples of secondary school students from form four until form six that who face with final examination. Set of questionnaire has been distributed to collect data. Then, data was analyzed by using the IBM Statistical Package for Social Science for Windows Version 19 (SPSS). It is including descriptive and inferential statistical such as mean score, frequency and percentage. Analysis of 147 responses using Pearson Correlation analysis revealed that there is a significant relationship between all of two stress dimensions factor to student self-esteem. The relationship between element of stress and the parent as a mediator effect indicated the significant value. However, the overall results showed that the purposed of this study can be beneficial for decision maker in school on evaluating the students stress factor. There were some limitations that have been identified underlying in this research investigated. From the research limitation described, it is proposed that future research to be carried out in order to cover the research area more thoroughly.